Doppler Finding, Cardiovascular Function Assessment, and Fetuses’ Survival Following the Fetoscopic Laser in Twin-to-Twin Transfusion Syndrome: Cardiovascular function and doppler assessing following TTTS laser - Ezazi Bojnordi, Tahmineh; Eslamian, Laleh; Marsoosi, Vajiheh; Golbabaei, Alireza; Sheikh Vatan, Mehrdad; Shamshirsaz, Alireza A.; Eshraghi, Nasim; Ghaemi, Marjan (Journal of Lasers in Medical Sciences, 2023)
Introduction: This study aimed to evaluate the effectiveness of selective laser photocoagulation of communicating vessels (SLPCV) on cardiac function in twins with twin-to-twin transfusion syndrome (TTTS). Methods: This retrospective cohort study evaluated 178 women with twin pregnancies complicated with TTTS and scheduled for SLPCV between 16 and 26 weeks of gestation. The severity of TTTS was determined by Quintero staging and the severity of cardiovascular disorders by the CHOP (Children’s Hospital of Philadelphia) score. Patient survival was evaluated through a one-monthafter-birth follow-up of fetuses. Results: The study revealed significant improvements in Doppler indices in both donors and recipients after SLPCV. The CHOP score also significantly decreased after the intervention. Onemonth after-birth survival rates were 55.1% in donors and 56.7% in recipients. Some Doppler indexes of fetuses before SLPCV could predict survival until one month after birth. Conclusion: The study suggests that SLPCV can improve cardiac function in fetuses with TTTS and that some Doppler indexes can predict survival outcomes. Additionally, the severity of TTTS can be a powerful indicator of the severity of cardiovascular complications.